2019
DOI: 10.1016/j.stemcr.2019.08.004
|View full text |Cite
|
Sign up to set email alerts
|

PSEN1ΔE9, APPswe, and APOE4 Confer Disparate Phenotypes in Human iPSC-Derived Microglia

Abstract: SummaryHere we elucidate the effect of Alzheimer disease (AD)-predisposing genetic backgrounds, APOE4, PSEN1ΔE9, and APPswe, on functionality of human microglia-like cells (iMGLs). We present a physiologically relevant high-yield protocol for producing iMGLs from induced pluripotent stem cells. Differentiation is directed with small molecules through primitive erythromyeloid progenitors to re-create microglial ontogeny from yolk sac. The iMGLs express microglial signature genes and respond to ADP with intracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
172
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(188 citation statements)
references
References 65 publications
14
172
1
1
Order By: Relevance
“…In the brain, ApoE4 is known to exacerbate microgliamediated neuroinflammation and subsequent neurodegeneration. 18,19 Peripherally, ApoE4 has also been shown to increase macrophage production of cytokine (eg, interleukin 6, tumor necrosis factor, compared to E2 or E3) in response to proinflammatory stimuli. 20 As cytokine storm is thought to account for COVID-19 disease manifestations, ApoE genotype may thereby augment disease severity by impacting host immune response.…”
Section: Increased Risk Of Poor Outcomes In Older People and Those Wimentioning
confidence: 99%
“…In the brain, ApoE4 is known to exacerbate microgliamediated neuroinflammation and subsequent neurodegeneration. 18,19 Peripherally, ApoE4 has also been shown to increase macrophage production of cytokine (eg, interleukin 6, tumor necrosis factor, compared to E2 or E3) in response to proinflammatory stimuli. 20 As cytokine storm is thought to account for COVID-19 disease manifestations, ApoE genotype may thereby augment disease severity by impacting host immune response.…”
Section: Increased Risk Of Poor Outcomes In Older People and Those Wimentioning
confidence: 99%
“…In Tarja Malm [94], Li-Huei Tsai [95] and Julia TCW (preprint, bioRxiv, doi: https://doi.org/10.1101/713362)'s studies using human iPSC-derived microglia models, they observed a dysfunctional or impaired phenotype of APOE4 iPSC-derived microglia when compared with that of APOE3, indicating that APOE4 might contribute to AD risk via dysregulating microglia. However, the opposite conclusion has been reported in another study performed with an murine microglial cell line [96].…”
Section: Discussionmentioning
confidence: 99%
“…Third, the protocol should be reproducible and reliable, within and between laboratories. On this point, there has been a limited effort to compare MGLs generated in any given protocol, to those generated by another, for example at the level of transcriptional profiling by RNA sequencing (115). A systematic comparison of such data across all protocols however, to the best of our knowledge, has yet to be performed.…”
Section: The Potential and Limitations Of Hipsc-derived Microglia Modmentioning
confidence: 99%
“…So far however, this only considers simple 2D monocultures of MGLs. This does offer the advantage of studying microglia phenotypes without interference from other cell types, as exemplified by recent work in the context of neurodegenerative diseases (63,115). It may equally be argued however, that important phenotypic information is also lost due to the absence of interactions with other cell types including neurons and astrocytes, which is also required for evaluation of synaptic pruning (116).…”
Section: The Potential and Limitations Of Hipsc-derived Microglia Modmentioning
confidence: 99%
See 1 more Smart Citation